2013
DOI: 10.1890/12-1602.1
|View full text |Cite
|
Sign up to set email alerts
|

Leaf traits within communities: Context may affect the mapping of traits to function

Abstract: Abstract. The leaf economics spectrum (LES) has revolutionized the way many ecologists think about quantifying plant ecological trade-offs. In particular, the LES has connected a clear functional trade-off (long-lived leaves with slow carbon capture vs. short-lived leaves with fast carbon capture) to a handful of easily measured leaf traits. Building on this work, community ecologists are now able to quickly assess species carbon-capture strategies, which may have implications for community-level patterns such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
109
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(118 citation statements)
references
References 25 publications
3
109
2
4
Order By: Relevance
“…SLA explained less variation in demographic rates than wood density or seed size (18,23) and that SLA values are variable and context-dependent (42,43). We also found that SLA and leaf N had stronger relationships with elasticities to fecundity than growth, an unexpected result given the strong positive correlation between these traits and relative growth rates (1).…”
mentioning
confidence: 53%
“…SLA explained less variation in demographic rates than wood density or seed size (18,23) and that SLA values are variable and context-dependent (42,43). We also found that SLA and leaf N had stronger relationships with elasticities to fecundity than growth, an unexpected result given the strong positive correlation between these traits and relative growth rates (1).…”
mentioning
confidence: 53%
“…Importantly, our detection of a single root trait spectrum linked to plant growth suggests that measuring one or two aspects of root growth morphology, such as root elongation rate, could be indicative of larger belowground strategies across species. Still, trait relationships may vary depending on resource availability (as demonstrated here) or on community types (Funk & Cornwell, 2013), and the traits measured in this study may not capture all aspects of seedling response to resource pulses, severe stress, or biotic interactions. Moving forward, it will be critical to explore and identify the scope of functional traits necessary to capture belowground strategies and plant responses, including plasticity-related metrics, across a range of ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, Funk and Cornwell (2013) argue that the strength of the LES relationships depends on the variation in leaf life span (LL). This variability in LL can be genetic and is often an adaptation to distinct climatic regimes or life-histories.…”
Section: Small-scale Studies and The Trait Variation Necessary For Thmentioning
confidence: 99%